Yowamushi pedal. 10 - Watanabe, Wataru, 1971- (Yen Press, LLC, 2018)
The third and final day of the inter-high is here, and Team Sohoku finished day two in second place. Can Onoda and his team use their last chance to overtake the leaders, or will an unexpected challenger spoil all their hopes? --